2020
DOI: 10.1371/journal.pone.0238780
|View full text |Cite
|
Sign up to set email alerts
|

Trends in population blood pressure and prevalence, awareness, treatment and control of hypertension among older persons: The 2006 & 2015 National Health and Morbidity Survey in Malaysia

Abstract: Background Hypertension is one of the most important risk factors for cardiovascular diseases. Thus, it is an important public health challenge worldwide. In Malaysia, only a few studies have focused on the trends of hypertension specifically for the aging population. In view of the rapid growth of the elderly population in Malaysia, there is an urgent need to explore the condition of hypertension in this aging population. Hence, the objectives of this study were to determine the trends of population mean syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Like in our study, among older adults in Malaysia, the prevalence of hypertension decreased significantly. [17] Possible reasons for the decrease in hypertension in Mongolia can be attributed to better control of hypertension, a decrease in current smoking, a decrease in frequent alcohol use, and an increase in fruit and vegetable consumption, despite an increase in overweight/obesity and physical inactivity. In Mongolia, the reduction of smoking, the reduction of high BP, and the reduction of poor fruit and vegetable intake can be attributed to tobacco demand-reduction measures, the increase in tobacco excise taxes, national salt/sodium policies, the management of major noncommunicable diseases, and the "drug therapy counseling for high-risk persons."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Like in our study, among older adults in Malaysia, the prevalence of hypertension decreased significantly. [17] Possible reasons for the decrease in hypertension in Mongolia can be attributed to better control of hypertension, a decrease in current smoking, a decrease in frequent alcohol use, and an increase in fruit and vegetable consumption, despite an increase in overweight/obesity and physical inactivity. In Mongolia, the reduction of smoking, the reduction of high BP, and the reduction of poor fruit and vegetable intake can be attributed to tobacco demand-reduction measures, the increase in tobacco excise taxes, national salt/sodium policies, the management of major noncommunicable diseases, and the "drug therapy counseling for high-risk persons."…”
Section: Discussionmentioning
confidence: 99%
“…Like in our study, among older adults in Malaysia, the prevalence of hypertension decreased significantly. [ 17 ] Possible reasons for the decrease in hypertension in Mongolia can be attributed to better control of hypertension, a decrease in current smoking, a decrease in frequent alcohol use, and an increase in fruit and vegetable consumption, despite an increase in overweight/obesity and physical inactivity. In Mongolia, the reduction of smoking, the reduction of high BP, and the reduction of poor fruit and vegetable intake can be attributed to tobacco demand-reduction measures, the increase in tobacco excise taxes, national salt/sodium policies, the management of major noncommunicable diseases, and the “drug therapy counseling for high-risk persons.” [ 21 , 22 ] The reduction of frequent alcohol use can be attributed to the strengthening of the national alcohol prevention and control programme in 2005, [ 23 ] and the “Together for Alcohol-Free Mongolia” campaign in 2011, [ 24 ] and an increase in body weight and physical inactivity can in part be attributed to no change in public awareness of diet and/or physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from our survey also showed that the overall proportion of patients who were aware of their diabetes condition was 39.29%; of those who were aware of their condition, 47.04% were receiving antidiabetic medication, which were lower than the results in developed countries, such as Latin America (79.8% awareness rate, 58.8% treatment rate), 24 Malaysia (65.2% awareness rate, 87.5% treatment rate) 25 and Switzerland (65.3% awareness rate, 86.0% treatment rate) 26 . The results is consistent with previous studies in China: rate of treatment was higher than previous study on population aged 18 years and over (25.8%), 3 and similar to study on adults aged 40 years or older in Jilin Province, Northeast China (47.7%) 27 .…”
Section: Discussionmentioning
confidence: 52%